Functions of Agrarian Families in the Prevention of Stunting: A Literature Review - Wariin, Sulton; Susanto, Tantut; Rahmawati, Iis (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: This research aims to identify factors related to the functions of agrarian families in rural areas that can contribute to the prevention of stunting. Methods: This study employs a literature review design with keywords "family" "agriculture or rural" and "stunting." The selection of articles follows the PRISMA approach. Articles were selected using three search engines: PubMed, Sage Journals, and Google Scholar. Results: This review summarizes eighteen articles. Nine articles discuss income and economic limitations within a family, ten articles explore food practices and dietary diversity (protein sources), three articles examine family size, four articles address maternal education and knowledge, three articles focus on exclusive breastfeeding, and two articles discuss parenting styles and early marriage culture, both considered influential in stunting within agrarian families in rural areas. Conclusion: Results Optimizable family functions in stunting prevention include economic, healthcare, reproductive, and socialization functions. Affective functions were not consistently found in the reviewed articles, possibly due to the limited use of three search engines by the researchers. Future researchers are encouraged to explore similar research themes using other journal search engines to enrich the study.